Squamous Cell Carcinoma Arising in a Mature Cystic Teratoma of the Ovary Presenting With a Ruptured Sister Mary Joseph Nodule: A Rare Case Report From Northern Tanzania - John Lugata; Caleigh Smith; Onesmo Mrosso; Jaynes Kabuhaya; Lily Severn; Krizia Nsoh Nji; Tecla Lyamuya; Elizabeth Skinner; Gilbert Nkya; Eusebious Maro; Alex Mremi; Bariki Mchome (Clinical Case Reports, 2026)
ABSTRACT Squamous cell carcinoma arising from malignant transformation of a mature cystic teratoma is an exceptionally rare ovarian malignancy, and metastatic umbilical involvement is particularly uncommon. Diagnosis and treatment planning are challenging due to overlapping presentation with epithelial ovarian cancer, particularly in settings with limited access to ancillary pathology, molecular testing, and specialist oncology services. We report a 54‐year‐old postmenopausal woman from northern Tanzania who presented with progressive abdominal distension and a spontaneously ruptured umbilical lesion with persistent discharge. Contrast‐enhanced computed tomography demonstrated a large complex right adnexal mass with calcifications and enhancing solid components, necrotic pelvic lymphadenopathy, peritoneal disease, and an umbilical lesion consistent with a Sister Mary Joseph nodule. Following multidisciplinary discussion and consideration of local diagnostic and financial constraints, she underwent exploratory laparotomy, total abdominal hysterectomy, bilateral salpingo‐oophorectomy, infracolic omentectomy, and wide excision of the umbilical lesion. Complete cytoreduction was not feasible due to unresectable rectal serosal and diffuse peritoneal disease. Histopathologic examination demonstrated well‐differentiated invasive squamous cell carcinoma arising within a mature cystic teratoma, with metastatic involvement of the omentum and umbilical skin. No cervical, uterine, or contralateral adnexal primary malignancy was identified. Immunohistochemistry was not performed because of limited local availability and cost; however, residual mature teratomatous elements adjacent to invasive keratinizing squamous cell carcinoma supported the diagnosis. She initiated adjuvant carboplatin‐paclitaxel chemotherapy following uneventful postoperative recovery. This case illustrates an unusual presentation of malignant transformation of mature cystic teratoma with cutaneous metastasis in a resource‐limited setting.